Bearing Capacity of Interfered Adjacent Strip Footings on Granular Bed Overlying Soft Clay: An Analytical Approach - Shivashankar, R.; Anaswara, S. (Salehan Institute of Higher Education, 2021)
In the present paper, the interference effects on bearing capacity of two and three closely spaced strip footings resting on granular bed overlying clay are being studied. A simple analytical model is proposed to predict the load-carrying capacity and the interference factor of an interfered footing, when adjacent strip footings are optimally placed on the surface of a Granular Bed (GB) overlying clay and both the footings are simultaneously loaded. A punching shear failure mechanism is envisaged in the analytical model. The load-carrying capacity of the footing is taken as the sum of total shearing resistances along the two vertical planes through the edges of the strip footing in the upper granular layer and the load-carrying capacity of the soft clay beneath the GB. Insights gained from finite element simulations are used to develop the new modified punching shear model for interfering footing. Bearing capacity can be easily calculated by using the proposed punching shear model for interfering footing. The analytical model is validated with numerical analyses and previous experimental results and found to be in reasonably good agreement. The influence of different parameters such as granular bed thickness, width of footing, number of footings are carried out in this study.Â Doi: 10.28991/cej-2021-03091723 Full Text: PDF